(untitled) (Международный научный журнал «Инженер», 2026)
The article reveals aspects of the concept of “sustainable urban planning”, which in the construction industry means orientation to the creation of multifunctional buildings and territories, intensive use of land resources and compact development, meeting the basic needs of society, creating comfortable living conditions for all population groups, as well as limiting the negative impact on the environment and protection of natural resources. It is proved that multifunctional residential complex is a new type of residential buildings. As a result of the performed researches the method of definition of the required public premises included in the complex is offered, variants of functional-planning structure of the building are established, which can be used to solve the main problems of formation of volume-planning solution of the multifunctional residential complex, proceeding from the town-planning peculiarities of the construction site.